2015
DOI: 10.1248/cpb.c15-00153
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Approaches for Sulfur Derivatives Containing 1,2,4-Triazine Moiety: Their Activity for <i>in Vitro</i> Screening towards Two Human Cancer Cell Lines

Abstract: A series of sulfur 1,2,4-triazine derivatives were prepared and evaluated as anticancer compounds for two human breast cancer cell lines (MCF-7, MDA-MB-231) with some of them acting as low micromolar inhibitors. Evaluation of the cytotoxicity using a 3-(4,5-dimethylthiazol-2-yl)-3,5-diphenyltetrazolium bromide (MTT) assay, the inhibition of [ 3 H]thymidine incorporation into DNA, and collagen synthesis inhibition demonstrated that these products exhibit cytotoxic effects on these breast cancer cell lines in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Therefore, the secondary amine group in 3a was alkylated to The most commonly used method to synthesize sulfonamide involves the reaction of sulfonyl chlorides with ammonia and amines in an alkaline environment [16,17]. This kind of synthesis has also been studied scientifically by our group, but the low yields prompted us to use the sulfenamide derivatives that are widely known for their medical applications [18][19][20].…”
Section: Synthesismentioning
confidence: 99%
“…Therefore, the secondary amine group in 3a was alkylated to The most commonly used method to synthesize sulfonamide involves the reaction of sulfonyl chlorides with ammonia and amines in an alkaline environment [16,17]. This kind of synthesis has also been studied scientifically by our group, but the low yields prompted us to use the sulfenamide derivatives that are widely known for their medical applications [18][19][20].…”
Section: Synthesismentioning
confidence: 99%
“…Recently, we have reported a series of sulfur 1,2,4-triazine derivatives and evaluated their as anticancer activity compounds against two human breast cancer cell line (MCF-7 and MDA-MB-231) [ 27 ]. The most effective compound was 5,5′,6,6′-tetraphenylbis(1,2,4-triazin-3-yl)disulfane acting as low micromolar inhibitors with IC 50 = 25 µM.…”
Section: Introductionmentioning
confidence: 99%
“…1 ), showed potential antitumor activity against breast cancer cells ( 19 ). Karczmarzyk, et al reported the synthesis and anticancer activity evaluation of a series of sulfur 1,2,4-triazine analogs and introduced 5,5′,6,6′-tetraphenyl-bis-(1,2,4-triazine)-3,3′-disulfide (2) as the most cytotoxic derivative ( 20 )…”
Section: Introductionmentioning
confidence: 99%